Production of Value-Added Chemicals by Bacillus methanolicus Strains Cultivated on Mannitol and Extracts of Seaweed Saccharina latissima at 50°C - Hakvåg, Sigrid; Nærdal, Ingemar; Heggeset, Tonje M. B.; Kristiansen, Kåre A.; Aasen, Inga M.; Brautaset, Trygve (Frontiers in Microbiology, 2020)
The facultative methylotroph Bacillus methanolicus MGA3 has previously been genetically engineered to overproduce the amino acids L-lysine and L-glutamate and their derivatives cadaverine and γ-aminobutyric acid (GABA) from methanol at 50°C. We here explored the potential of utilizing the sugar alcohol mannitol and seaweed extract (SWE) containing mannitol, as alternative feedstocks for production of chemicals by fermentation using B. methanolicus. Extracts of the brown algae Saccharina latissima harvested in the Trondheim Fjord in Norway were prepared and found to contain 12–13 g/l of mannitol, with conductivities corresponding to a salt content of ∼2% NaCl. Initially, 12 B. methanolicus wild type strains were tested for tolerance to various SWE concentrations, and some strains including MGA3 could grow on 50% SWE medium. Non-methylotrophic and methylotrophic growth of B. methanolicus rely on differences in regulation of metabolic pathways, and we compared production titers of GABA and cadaverine under such growth conditions. Shake flask experiments showed that recombinant MGA3 strains could produce similar and higher titers of cadaverine during growth on 50% SWE and mannitol, compared to on methanol. GABA production levels under these conditions were however low compared to growth on methanol. We present the first fed-batch mannitol fermentation of B. methanolicus and production of 6.3 g/l cadaverine. Finally, we constructed a recombinant MGA3 strain synthesizing the C30 terpenoids 4,4′-diaponeurosporene and 4,4′-diapolycopene, experimentally confirming that B. methanolicus has a functional methylerythritol phosphate (MEP) pathway. Together, our results contribute to extending the range of both the feedstocks for growth and products that can be synthesized by B. methanolicus.